Decentralized Re-Platforming: a case study of three fediverse instances - Foletto, Leonardo; Flynn, Guilherme (AoIR Selected Papers of Internet Research, 2026)
The Fediverse, a decentralized network of social platforms interconnected via protocols like ActivityPub, has gained traction amid crises in centralized platforms, such as Elon Musk’s acquisition of Twitter/X in 2023 and Meta’s 2025 changes in content moderation". This migration, termed “decentralized replatforming,” represents a horizontal shift where users voluntarily leave toxic spaces for federated networks like Mastodon and Pixelfed. While decentralization allows customizable moderation rules, it also creates challenges in scalability, resource allocation, and combating disinformation. This study investigates these tensions through semi-structured interviews with maintainers of Fediverse instances (Hubzilla.com.br, Bolha, Milpa), focusing on governance, costs, and ethical dilemmas. Preliminary findings reveal a heterogeneous migration: Bolha attracts progressive users fleeing hate speech, while Hubzilla serves as a technical refuge. The research proposes “decentralized replatforming” as a concept capturing both escape from corporate platforms and experimentation with alternative models. Key challenges include balancing autonomy with collective responsibility and ensuring sustainability without replicating Big Tech’s centralization. The study highlights the Fediverse as a contested space for ethical and technical innovation in digital communication.